Dichronic study of oid terminations to build hydraulic inshorations in various systemic languages - Bobaqulova Luiza Ravshanovna (Zien Journals, 2022)
Hydroelectric - technical sciences are a source of water resources (dry, blue, sea, ore an, earth's surface, and atosphere water) bring fyodalnysh and water for the needy hydroelectric power plants that are used for these arguments and inshohlash and construction issues n. Construction of hydroelectric power plants k it's multi-ditch and wide. Water is taken up through the tree's roots and transported to the leaves by a sophisticated surface. annish (hydroenergy), maintenance, maintenance , ri and bshqlers entered. The total amount of water resources on earth is 1.3 billion square miles [1.3 billion sq km], so 97.2% of drinking is irregular water. 2.15% is water in the glacier or 0.65% of the water was poured into the nigin.
Keywords: knol; nov; aquaducts; dyuker